2016
DOI: 10.5812/pedinfect.39193
|View full text |Cite
|
Sign up to set email alerts
|

Strain Typing and Molecular Characterization of CTX-M-1 Group ESBL in Clinical Klebsiella pneumoniae Isolated from Children

Abstract: Background: Extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae is rapidly spreading worldwide, creating se-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…24 In another study in Kurdistan, Iran, PFGE analysis of K. pneumoniae isolates was performed, and they identified 11 various profiles and one major clone, and transmission between patients and different wards was also proposed. 36 According to a previous study, environmental reservoirs in hospitals can cause the transmission of different bacteria and antibiotic resistance in different wards. 25 As previously reported, antimicrobial resistance genes can easily spread among different species and strains and distribute among the hospital wards.…”
Section: Discussionmentioning
confidence: 99%
“…24 In another study in Kurdistan, Iran, PFGE analysis of K. pneumoniae isolates was performed, and they identified 11 various profiles and one major clone, and transmission between patients and different wards was also proposed. 36 According to a previous study, environmental reservoirs in hospitals can cause the transmission of different bacteria and antibiotic resistance in different wards. 25 As previously reported, antimicrobial resistance genes can easily spread among different species and strains and distribute among the hospital wards.…”
Section: Discussionmentioning
confidence: 99%
“…Expanded-spectrum cephalosporins are still among the most globally prescribed antimicrobial agents [5]. This extensive usage has been mirrored by a global expansion of extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae showing resistance to ceftriaxone, cefotaxime, ceftazidime, and monobactams (as aztreonam), reaching 50% in some countries [4,6]. At a national level, a surveillance study carried out in five hospitals in Cairo, from 1999 to 2000, showed reduced susceptibility of Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the repetitive use of cefotaxime and ceftazidime in therapy regimens for infections due to ESBL-producing K. pneumoniae has induced the emergence of K. pneumoniae harboring the most widespread type of ESBLs, the CTX-M-β-lactamases [6]. Based on their amino acid sequence identities, this group of molecular class A ESBLs has been subdivided into five clusters (from Group I to Group V) all possessing superior hydrolytic activity against ceftriaxone and cefotaxime [9] rather than ceftazidime [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations